ANALISIS PUBLIKASI KEBUN RAYA BOGOR TAHUN 1994 -2012 (THE ANALYSIS OF BOGOR BOTANICAL GARDEN PUBLICATION FROM 1994 – 2012) - Rahayu, Rochani (Direktorat Repositori, Multimedia, dan Penerbitan Ilmiah - Badan Riset dan Inovasi Nasional (BRIN Publishing), 2014)
This study aims to evaluate: 1) the amount and kinds of publications in Bogor Botanical Garden Publication from1994 to 2012; 2) the subjects of the publication; 3) the publishers’ name; 4) the language used in the publication; 5)the author’s sex; 6) author collaboration index; and 7) the media used in the publication. The descriptive studi usedata source of Publikasi Kebun Raya Bogor tahun 1994 -2012 published by Pusat Konservasi Kebun Raya Bogor,2012. Data of publication frequency were the presented in tables and graphs.The results showed that: 1) The bookwas in the 1 rank (41 titles; 63.08%), secondary literatures in the second rank (17 titles; 26.16%), the third rank it wasproceedings ( 4 titles; 6.16%), a total of 3 titles (4.6%) of journals were in the last posisition; 2) It found 3 ranks fieldsi.e. botanical gardens in the first place ( 21 titles; 32.31%), secondly was floras (13 titles; 20%) and thirdly wasmedicinal plants (9 titles ; 13.85%) 3). The first rank of the publisher was Kebun Raya Bogor (47 titles; 72.71%),second rank was LIPI Press (7 titels; 10.77%). The third rank was Kebun Raya Bogor collaboration with Bank Mandiri(2 titles; 3.08%) and Kebun Raya Bogor collaboration with Chevron Foundation (2 titles ; 3.08%). It found that onepublisher have no name and one publisher came from abroad i.e. Tokyo National Museum. 4) It showed that a totalof 54 publications (83.08%) was in Bahasa Indonesia 7 titles (10.77%) of publications was in English, 1 publication(1.54%) was in Japanese, 3 publications (4.65%) was in two languages (Bahasa Indonesia and English). 5) Base on62 titles of publication out of journal found that there were 145 authors consist of 55 mens (37.94%) and 90 womens (62.06%). 6). It of showed that author collaboration index was 2.33. 7) It found that all of the books, proceedings andjournals were in printed. The secondary literatures found that printed document was in the first rank ( 10 titles;58,83%), secondly it was printed in combined with electronics (5 titles; 29,42%) and thirdly it was in electronics (2titles; 11.77%). Conclusion from this study it found that Kebun Raya Bogor was the active institutions in thegenerate a lot of publications.